2023
DOI: 10.1371/journal.pone.0289646
|View full text |Cite
|
Sign up to set email alerts
|

Impact of height difference between coronary ostium and location of intracoronary pressure sensor on fractional flow reserve measurements

Moon-Seung Soh,
Hangyul Kim,
Min Gyu Kang
et al.

Abstract: Background During fractional flow reserve (FFR) measurements, distal coronary pressure (Pd) can be influenced by hydrostatic pressure changes resulting from the height difference (HD) between the coronary ostium and the location of the distal pressure sensor. Aims We investigated the effect of aortocoronary HD on the FFR measurements in each coronary artery. Methods In this retrospective cohort study, we analyzed 257 patients who underwent FFR measurements and coronary computed tomography (CCTA) within a y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Harle et al used a dynamic flow simulator to perform in vitro measurements and showed a correlation between absolute pressure differences and coronary height differences [ 8 ]. Other studies used recorded pressure measurements and compared the actual pressure ratios with pressure ratios corrected for hydrostatic pressure showing a reclassification of 12–13% for FFR and 20–27% for non-hyperaemic pressure ratios [ 13 , 14 , 15 ]. One study used an animal model and took FFR measurements during various height differences between the guide catheter tip and the distal pressure wire sensor produced by body rotation (20° to the right and 25° to the left) with or without vertical inclination (10° above and 10° below) of the catheterisation bed [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harle et al used a dynamic flow simulator to perform in vitro measurements and showed a correlation between absolute pressure differences and coronary height differences [ 8 ]. Other studies used recorded pressure measurements and compared the actual pressure ratios with pressure ratios corrected for hydrostatic pressure showing a reclassification of 12–13% for FFR and 20–27% for non-hyperaemic pressure ratios [ 13 , 14 , 15 ]. One study used an animal model and took FFR measurements during various height differences between the guide catheter tip and the distal pressure wire sensor produced by body rotation (20° to the right and 25° to the left) with or without vertical inclination (10° above and 10° below) of the catheterisation bed [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, this hydrostatic pressure effect is ignored, as the actual pressure gradient is usually small (<5 mmHg) [ 9 ]. Nevertheless, recent studies have suggested that the hydrostatic pressure gradient influences significantly pressure-based physiological indices [ 7 , 10 , 11 , 12 , 13 , 14 , 15 ], and as such the quantification of the hydrostatic impact on clinical practice remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%